Prevalence of sarcopenia, empty nest, depressive symptoms and its association with diet quality among older adults with low socioeconomic status in Kelantan - Nazri, Nurul Syahiidah Mohd (2022)
Aging itself increases the risk of poor diet quality among older adults due to chronic disease, psychosocial problems, physical limitations and loneliness. Older adults with low socioeconomic status are at higher risk of health problems. Therefore, the current study aimed to assess the association between sarcopenia, empty nest and depressive symptoms with diet quality among older adults with low socioeconomic status. A total of 293 older adults in five districts in Kelantan namely Pasir Mas, Bachok, Tumpat, Kota Bharu and Machang were recruited in the study. Study subjects who fulfilled the inclusion criteria (aged 60 years and above, low education level, B40 group, have no health problems that will limit ability to perform physical fitness tests) were selected through convenience sampling method. Data on socio-demography, anthropometry, body composition, medical history, blood pressure, depressive symptoms, empty nest, diet history and sarcopenia were obtained through interview administered method. Most of the subjects were married (69.6%), are of Malay ethnicity (100%) and has income less than RM900 (91.5%). The prevalence of empty nest was 30.7%. Almost half of the subjects were underweight (48.8%). The prevalence of sarcopenia and severe sarcopenia were 22.2% and 18.8% respectively. The prevalence of high risk of depressive symptoms is 28.3%. Both men and women did not meet the recommendation for daily energy intake. Healthy Eating Index (HEI) score revealed that 42% of the subjects had poor diet quality, 57% need improvement in their diet and only 1% had good diet quality. HEI score was significantly higher in subject with no sarcopenia as compared to those who were sarcopenic and severe sarcopenic. Binary logistic regression revealed that subjects with high cholesterol were 2.4 times more likely to exhibit poor diet quality than those with normal cholesterol level (95% CI: 1.107, 5.209; p-value: 0.027). Increasing Short Physical Performance Battery (SPPB) score was associated with a reduction in the likelihood of exhibiting poor diet quality (OR:0.780; 95%CI: 0.624-0.974; p-value:0.028). In conclusion, the prevalence of sarcopenia, empty nest, and subjects with high risk of depressive symptoms among the study subjects were considerably high. The dietary intake among older adults is also worrying especially regarding fruits and vegetables intake. Thus, nutrition interventions especially in increasing knowledge and skills of older adults to ensure healthy eating are essential to help older adults with low socioeconomic status to improve their nutritional status for reducing risk of sarcopenia and chronic diseases.